Analisis Moralitas Socrates Dalam Perspektif Filsafat Hukum - Kayla Fausta Natania Sada; Amelia; Feybiola Cecilia Mahieu; Yuwono Prianto (Lembaga Teewan Journal Solutions, 2026)
This study examines the concept of morality according to Socrates and its relevance in legal philosophy. It is based on the idea that law is often seen merely as rules, whereas it should also reflect justice and moral values. This research uses a normative legal method with a conceptual approach through literature study. The results show that, according to Socrates, morality is closely related to knowledge and rationality. Virtue is understood as knowledge of the good, meaning that those who understand goodness will act rightly. In legal philosophy, this view emphasises that law cannot be separated from morality. Laws without moral foundations risk losing their sense of justice. Therefore, an ideal law should reflect goodness and justice. In conclusion, morality plays an important role in shaping and evaluating law to ensure it remains fair and relevant in society.